Transcriptomic Analysis of the Interaction Between FLOWERING LOCUS T Induction and Photoperiodic Signaling in Response to Spaceflight - Wang, Lihua; Xie, Junyan; Mou, Chenghong; Jiao, Yuwei; Dou, Yanhui; Zheng, Huiqiong (Frontiers in Cell and Developmental Biology, 2022)
Spaceflight has an impact on the growth and development of higher plants at both the vegetative stage and reproductive stage. A great deal of information has been available on the vegetative stage in space, but relatively little is known about the influence of spaceflight on plants at the reproductive stage. In this study, we constructed transgenic Arabidopsis thaliana plants expressing the flowering control gene, FLOWERING LOCUS T (FT), together with the green fluorescent protein gene (GFP) under control of a heat shock-inducible promoter (HSP17.4), by which we induced FT expression inflight through remote controlling heat shock (HS) treatment. Inflight photography data showed that induction of FT expression in transgenic plants in space under non-inductive short-day conditions could promote flowering and reduce the length of the inflorescence stem in comparison with that of wild-type plants under the same conditions. Whole-genome microarray analysis of gene expression changes in leaves of wild-type and these transgenic plants grown under the long-day and short-day photoperiod conditions in space indicated that the function of the photoperiod-related spaceflight responsive genes is mainly involved in protein synthesis and post-translation protein modulation, notably protein phosphorylation. In addition, changes of the circadian component of gene expression in response to spaceflight under different photoperiods indicated that roles of the circadian oscillator could act as integrators of spaceflight response and photoperiodic signals in Arabidopsis plants grown in space.